STRATEGI PENGUATAN KAPASITAS SUMBER DAYA MANUSIA LEMBAGA PENYELENGGARA PEMILIHAN UMUM - Muslimah, Siti; Hermawan, Dedy; Efendi, Nur (Journal of Policy & Bureaucracy Management, 2021)
The General Elections Supervisory (BAWASLU) plays a role in supervising the implementation of elections in accordance with the laws and regulations in order to realize people's sovereignty as well as the application of democratic principles or values ​​for the realization of the ideals of a democratic Indonesian society. This research is a qualitative descriptive study which choose the BAWASLU Office of South Lampung Regency as a research location. The focus of the research is the strategy of strengthening human resource capacity by using a strategic management process. The purpose of the research is to find out how the strategy is to increase the human resource capacity of the elections Bawaslu of South Lampung Regency. The results of the study indicate that the strategy carried out by the Bawaslu of South Lampung Regency has been running in accordance with the strategic planning made. Based on the SWOT analysis, which produces quadrant I, which supports an aggressive strategy, it shows that the Bawaslu of South Lampung Regency has great strengths and opportunities in favorable situations so that they can take advantage of existing opportunities and minimize weaknesses and threats around them.